ANALISIS EFISIENSI BELANJA DAERAH DI JAWA TIMUR ( STUDI KASUS BIDANG PENDIDIKAN DAN KESEHATAN TAHUN 2009-2011) - Lestari, Triyanti; Khusaini, Moh. (Jurnal Ilmiah Mahasiswa FEB, 2012)
Fiscal decentralization in Indonesia is more focused on the expenditure side. Region are given considerable authority to spend the funds. And in almost all regions in Indonesia, including East Java has increased spending every year. With the increase in the expenditure should be followed by an increase in output, but not necessarily as it happens. Spending efficiency is an important issue in the public sector policy, expenditure which efficient is believed can encourage an increase in the welfare. The purpose of this study is to analyze the efficiency of public spending in East Java, especially education and health spending. This study uses the data on period 2009-2011, covering 10 districts / cities in East Java and uses Data Envelopment Analysis. Input variables used are education spending and health spending. Output variables for education using the number of schools, number of teachers and number of students, and for health use a number of puskesmas (health centers), the number of health workers in puskesmas (health centers) and number of immunization. Based on calculations by the DEA found that the efficiency score varies in each region and in general there are many region which their spending have not been efficient. Education spending is still better than health spending. And Malang is the most efficient and Surabaya is the most inefficient among the ten regions studied. Some improvement in each variable is still required for areas that have not been efficient. Kata Kunci : Efisiensi, Belanja Pendidikan, Belanja Kesehatan, Data Envelopment Analysis